Implementação de uma política pública de letramento: análise sobre o Programa Sala e Espaço de Leitura da rede municipal de São Paulo - Firmino, Estevao Marcos Armada [UNIFESP] (2020)
This research analyzes the process of implementing the Reading Room Area Program, a public literacy policy, which links the development of skills and abilities to the transmission of values, through participation in social practices related to written culture, specifically through access to Literary production. The theoretical framework mobilized in this study had the contributions of Literacy Studies (STREET, 2014; BARTON, 2000; KALMAN, 2004) and the field of implementation of public policies (LIPSKY, 2019; HAM; HILL, 1993; ARRETCHE, 2001; LOTTA, 2018). It is also supported by contributions by authors that address inequalities in access to written culture and schooling (SOARES, 2010; BATISTA and RIBEIRO, 2004), reading as an object of study (BATISTA and GALVÃO, 2005), and school literacy (BUNZEN, 2010; DIONÍSIO, 2000). For analysis purposes, it was outlined the background of this policy, analyzing its regulatory and implementation configurations. Besides, through the analysis of interviews, the perception of three agents of the Program on aspects present in the implementation of this policy was examined, such as their adherence to the objectives and guidelines of the policy, processes of interaction and institutional context and discretion. Also, contributing to the analysis and educational ethnography (ROCKWELL, 2011) was undertaken in classes at a Reading Room located in Cidade Tiradentes neighborhood São Paulo state to monitor the implementation of the policy. As a result, changes in the format of the SAEL Reading Space Program were evidenced, resulting from the change in the ways of conceiving reading in the school area, in addition to adaptations of strategies to meet its contemporary demands, such as attention to the training of agents and attribution of relevance to the collection Reading Rooms. The analysis of the interviews with agents implementing the policy revealed adherence to the SAEL Reading Area Program guidelines. Concomitantly, attention to the agents' training processes was shown to be imperative for an alignment of all public policy strategies. The agents' interaction processes within the Program also show the need for adjustments. In the context of the research, it was identified three literacy practices (book loans, sharing readings, and a book exchange fair) that are very significant for the Reading Room Guiding Teacher and students, revealing the mobilization of particular strategies of meanings linked to the distribution of resources and social goods that meet the objectives of this public policy.